Pemberdayaan Masyarakat melalui Pembentukaan Skema Pembiayaan Kesehatan Pra Upaya untuk Penyakit Kronis - Herni Hasifah; Rafi’ah Rafi’ah; Iga Maliga (Lembaga Pengembangan Kinerja Dosen, 2026)
The biggest challenge faced by the community, especially vulnerable and poor groups, is the cost of managing chronic diseases. Even though there is national health insurance, non-medical costs, costs arising from self-medication, and limitations on certain benefits are still often obstacles that cause high out-of-pocket expenses for the community. The high costs of curative and rehabilitative care indicate that preventive and promotive efforts must be significantly improved, and one way to support the sustainability of these efforts is through a pre-emptive health financing scheme. Community service activities are carried out using a participatory approach so that community members are actively involved in the activities. The activities are carried out in three stages, that is preparation or needs identification, implementation and evaluation. The results of the activity show that the community's knowledge increased significantly because of the community service activity. Participants who took part in the activity also successfully designed a community-based financing scheme involving health savings, whereby each member makes agreed monthly contributions. This community service project demonstrates that community empowerment through the establishment of a pre-emptive financing scheme for chronic diseases can provide an effective, sustainable solution for improving public health.